Effectiveness of Structured Teaching Program on Menstrual Hygiene among Adolescent School Girls - Bajracharya, Srishti; Bam, Pratibha; Bajracharya, Priyanka (Journal of Lumbini Medical College, 2020)
Introduction: Adolescent girls face different physical conversions, sexual changes and psychological pressures associated with growth and maturity, menstruation being one of them. Menstruation is still clouded by taboos and socio-cultural restrictions resulting in ignorance of scientific facts and hygienic health practices. Since response to menstruation depends upon awareness and knowledge about issues, menstrual hygiene education has shown to be effective in improving health by developing good knowledge, attitude and practice among adolescent girls. Methods: An analytical study with one group pretest – posttest design was carried out to assess the effectiveness of structured teaching program on menstrual hygiene among 100 adolescent school girls studying in a public school in Palpa. Pretested semi structured questionnaire was used to assess knowledge and practice whereas valid MAQ (Menstrual Attitude Questionnaire) was used for attitude. This was followed by structured teaching program consisting of information on menstruation, myths and hygiene. Then a post-test was conducted after a week to the same respondents. Results: The study resulted in statistically significant improvements (P<0.001) in total knowledge (63% to 66%), attitude (47% to 63%) and practice (43% to 49%) after implementation of the structured teaching program. There was positive correlation between knowledge and attitude scores (r=0.023), attitude and practice scores (r=0.026) and knowledge and practice scores (r=0.183). Conclusion: The structured teaching program is effective in improving knowledge, attitude and practice on menstrual hygiene among adolescent school girls. Thus, adding menstrual hygiene as part of curriculum may break the culture of silence.